Effect of the Carbon Source and Plant Growth Regulators (PGRs) in the Induction and Maintenance of an In Vitro Callus Culture of Taraxacum officinale (L) Weber Ex F.H. Wigg - María Eugenia Martinez; Lorena Jorquera; Paola Poirrier; Katy Díaz; Rolando Chamy (Agronomy, 2021)
Taraxacum officinale (L.) Weber ex F.H. Wigg, commonly known as dandelion, is a cosmopolitan and perennial weed, which has medicinal properties. In vitro propagation methods are widely used on plants that have difficulties in cultivation and, consequently, low extraction yields of active metabolites. Thus, callus culture has been considered to be useful for the accumulation of several metabolites. In this study, we aimed to establish an efficient protocol for callus induction and maintenance of T. officinale, for which explant type, carbon source, light conditions, and nine different combinations of plant growth regulators (PGRs), such as 1-naphthaleneacetic acid (NAA) (from 0.05 to 0.5 mg/L) and 6-benzylaminopurine acid (BAP) (from 0.5 to 3.0 mg/L), were evaluated. The results showed that hypocotyls and roots from sterile seedlings are the best sources for callus induction, with 100% of callogenesis at every condition tested, and more than 95% of viability and friability. Complete darkness and a medium supplemented with sucrose at 2.3% (w/v) and 0.5 mg/L of NAA and 0.5 mg/L of BAP were the best conditions for callus induction, showing callus with low organogenesis and high friability. This study provides a basis for future studies on improving large-scale callus propagation and further establishment of suspension culture systems for commercial purposes.